ChemInform Abstract: Alternative Hydrogen Source for Asymmetric Transfer Hydrogenation in the Reduction of Ketones. Issue 17 (April 2016) - Wakeham, Russell J.; Morris, James A.; Williams, Jonathan M. J.
Abstract: The application of cis‐1, 4‐butenediol as a hydrogen source for the asymmetric transfer hydrogenation of ketones (I) and (III) is reported.